Acetabular Central Fracture Dislocation after Generalized Seizure during Lumbar Myelography with Iohexol. (2nd April 2013) - Park, Kyung-Soon; Moon, Jae-Young; Oh, Chang-Seon; Yoon, Taek-Rim
Abstract : Fracture is a less common complication in seizure patients, and fractures as a consequence of convulsive seizures without direct trauma occur in 0.3% of cases. Acetabular fractures after convulsions are even more rare, and only a few cases of acetabular fracture dislocations, purely caused by convulsive activity, have been reported. Therefore, we report a case of unilateral acetabular central fracture dislocation after a seizure episode, with relevant literature review. The seizure attack occurred after contrast media (Iohexol) injection for checking the myelography.